Substrate specificity of pyrophosphate:fructose 6-phosphate 1-phosphotransferase from potato tuber. - Montavon, P; Kruger, N (1992)
The aim of this work was to establish the precise ionic form of the reactants used by pyrophosphate:fructose-6-phosphate phosphotransferase. The enzyme was purified to near-homogeneity from potato (Solanum tuberosum L.) tubers. Changes in enzyme activity when the pH of the assay and the concentration of fructose 6-phosphate, pyrophosphate, and magnesium are varied independently indicate that fructose 6-phosphate(2-) and MgP(2)O(7) (2-) are the reacting species in the glycolytic direction. Analogous experiments with fructose 1,6-bisphosphate, inorganic phosphate, and magnesium demonstrate that the enzyme uses fructose 1,6-bisphosphate(4-), HPO(4) (2-), and Mg(2+) in the gluconeogenic direction. The ionic species used in the glycolytic direction are comparable with those required by bacterial ATP-dependent phosphofructokinase. This is consistent with the proposal that the active site of pyrophosphate:fructose-6-phosphate phosphotransferase in plants is equivalent to that of the bacterial phosphofructokinase (SM Carlisle et al. [1990] J Biol Chem 265: 18366-18371).